(untitled) (International Journal of Physiotherapy, 2015)
Background: Recently the exercises and fitness professionals have adopted water as an alternative medium for delivering programs to improve fitness and health. When exercise on dry land our skeletal muscular, cardiovascular, respiratory and other body systems are greatly affected by the forces of gravity. When exercise in water, the effects created by the gravitational pull on the body are attenuated. Therefore the aim of this study was to determine the effectiveness of land based endurance training and aquatic based endurance training for enhancing endurance in normal individuals. Methods: An experimental study design with 30 subjects healthy individuals between 20-30 years of both sexes currently were divided equally into 2 groups. Group A underwent land based exercises while Group B underwent aquatic based exercises. The outcome measures consist of RPP (rate pressure product), REC HR (recovery heart rate), RHR (resting heart rate) and 6MWD (6 minute walking distance) was measured before (pre-training) and after four weeks of endurance training. Results: In this study, the mean improvement between the 2 groups of land and aquatic based endurance exercises were tested for significance using a dependent t test. The calculated t value were 43.550, 4.583, 16, 5.870 for RPP, REC HR, RHR, 6MWD for group A respectively. For group B 25.922, 12.762, 27.495,19.236 for RPP, REC HR, RHR, 6MWD for group A respectively with p<0.05. This clearly indicated that both land based exercises and aquatic based exercises will improve cardiovascular endurance significantly and there is no significant difference between land based exercises and aquatic based exercises for enhancing endurance in normal individuals. Conclusion: It is concluded that both land based and aquatic based endurance exercises methods produce equivalent, if not same effect on the enhancement of aerobic endurance. There was no significant difference between these two exercising mediums. Nonetheless, given the benefits of aquatic medium, aquatic based endurance exercises should be considered as an alternative for land based training.